Interrelation of Authorities and Business on the Municipal Level: Practices in Kemerovskaya Oblast - Маргарита Владимировна Курбатова; Сергей Николаевич Левин; Наталья Федоровна Апарина (Journal of Economic Sociology, 2010)
The creation of the favorable conditions for the business development depends on the search of the opportunities to increase effectiveness of the interaction with regional and local authorities. Different regions have their own practices. The authors assume that there is a difference between the normative picture of the business-authorities relations derived from the formal norms of the country and the real institutional model depicted from the formal and informal rules of interaction between authorities and business in a particular region. The research is focused on the real institutional model of business and authorities interaction on municipal level. The federal level is considered as a main source of formal norms and a source of problems that are solved by the regional and municipal authorities in the process of interaction with business. The regional level is considered as the source of the informal norms and basic practices that frame the conditions of the authorities and business interaction on the municipal level.